Evaluación pre cosecha – cosecha y postcosecha del cultivo de maíz (zea mays l.) para la inocuidad en las parroquias de lucero y san güillín cantón calvas, provincia de Loja. - Torres Pardo, Fernando Darío (2021)
Corn, a basic product for human consumption and raw material for many derivatives, merits a study on the inadequate use of agrochemicals in order to increase its production, affecting food security worldwide and in our country. The main varieties cultivated in the parishes of Lucero and San Güillín, Calvas canton, province of Loja, are: DK-7088, Triunfo, Brasilia and Criollo. This research consists of a pre-harvest, harvest and post-harvest evaluation of the corn crop in order to analyze the safety of the product obtained from the application of chemical inputs and their management from its physiological maturity as a post-harvest management strategy. The results obtained through direct monitoring of the agents of the production chain in the various stages and procedures for the application of inputs were: overdosage of Killer, Nuvan 100 EC®, Semevin, Malathion 57% EC and Phostoxin®; This problem influences the production and quality of the grain, which is marketed as raw material for the production of concentrated food (balanced), destined for the animal industry, becoming an important link for the socioeconomic development of the canton and the country. Once the problems were identified, a proposal was generated to correct these shortcomings in a technical and well-founded manner in order to obtain a higher production of higher quality and with safety standards.